Manual de ética profesional dirigido a los estudiantes de la carrera de licenciatura en Parvularia en la universidad técnica de Cotopaxi, del cantón Latacunga, parroquia la matriz, en el año lectivo 2012-2013 - Cárdenas Jiménez, Yajaira Katherine (2014)
The handbook of ethics contribute practical activities aimed at early childhood education career , with this guide to ethical ideas that serve as support for the actions of the students , managing to have a successful teaching practice in infant classrooms they might. Whereas at the age of 0-6 years is specifically the adult stage is formed; and the teacher should be a living example of ethical behavior in the spirit, conscious of the responsibility. This basic instrument to consolidate the educational values of our future teaching. Ethical training based on the internalization of a given moral system through a process of construction personnel aware, contextualized and active, where the future nursery teacher should generate new attitudes of personal growth and development, and for this reason all perfects activity and consequently a process of teaching and service excellence ultimately resulting in the learner a structured knowledge is obtained. The Ethics Manual for preschool students is the beginning of an awareness of the importance of the contribution of teacher training in human theoretical framework which divided into three parts presents "Ethical Principles, educator Century XXI and the Role of the Teacher. "Which an area of" Pedagogical and Didactic Applications" , in which reflections and activities for the development of ethical sense within the students discover career unfolded